Using the Supply-Chain Management for Developing Oil Indiutries in the Republic of Kazakhstan - R Mugauina; D. Madiyarova; Shishmanov Krasimir (International Journal of Supply Chain Management, 2020)
Abstract- The oil and gas industry is involved in a global supply-chain that includes domestic and international transportation, ordering and inventory visibility and control, materials handling, import/export facilitation and information technology. Thus, the industry offers a classic model for implementing supply-chain management techniques. In a supply-chain, a company is linked to its upstream suppliers and downstream distributors as materials, information, and capital flow through the supply-chain. The purpose of this paper is to investigate the role of supply-chain management in the oil and gas industry. The challenges of a growing innovative economy impose the need to consider the context of the analyzed area with the characteristics of a mono-raw oil and gas group in a sparsely populated territory by supply chain strategy. The paper considers the key factors for reducing costs and increasing the company’s profits in managing supply chains: demand management, efficient distribution of petroleum products among customers, better transportation scheduling, warehouse management, and quality and timeliness of information through the automation of the supply chain. Revising the ways to expand the production capabilities will ensure the achievement of sustainable development of the Atyrau region not only in the medium but also in the long-term perspectives when oil is replaced by other sources, which will make the region less attractive for investors. Results show that implementation of supply-chain management in the oil industry can help to reduce costs, increase the company’s profits in managing supply, and manage the planning of deliveries.